Fiber non-linear effects in multiple-wavelengths optical CDMA systems - Kharazi, Seyed Mohammad Saleh Seyedzadeh; Sahbudin, Ratna Kalos Zakiah; Abas, Ahmad Fauzi; Ahmad Anas, Siti Barirah (Institution of Electronics and Telecommunication Engineers, 2013)
Multi-wavelength Optical Code Division Multiple Access (OCDMA) systems suffer from fiber impairments including non-linear effects (NLE), especially when the number of wavelengths and input power level increase. In this paper, a review of NLE, including self-phase modulation, cross-phase modulation, four wave mixing (FWM), stimulated Brillouin scattering and stimulated Raman scattering on the system performance of OCDMA systems is presented. As some of the non-linearities may have correlated effects on the performance of the system, the relations between these effects are also investigated. Bit error rate results reveal that the most important unwanted effect was caused by FWM.